2012
DOI: 10.1111/j.1365-2265.2012.04339.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin measurement during inferior petrosal sinus sampling improves the localization of pituitary adenomas in Cushing's disease

Abstract: Prolactin measurement, during IPSS, improves our ability to correctly localize the pituitary adenoma site in CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 27 publications
(82 reference statements)
1
26
0
2
Order By: Relevance
“…In our study, the determination of lateralization was directly from plasma ACTH levels. However, previous studies have shown that by simultaneously measuring prolactin levels, a correction can be carried out to validate the integrity of pituitary venous effluent, helping to validate the presence or absence of an ACTH‐secreting pituitary tumour . Prolactin measurement can even reveal false‐negative lateralization .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the determination of lateralization was directly from plasma ACTH levels. However, previous studies have shown that by simultaneously measuring prolactin levels, a correction can be carried out to validate the integrity of pituitary venous effluent, helping to validate the presence or absence of an ACTH‐secreting pituitary tumour . Prolactin measurement can even reveal false‐negative lateralization .…”
Section: Discussionmentioning
confidence: 99%
“…75,110 The relative concentration of prolactin in the inferior petrosal sinus blood compared with the peripheral blood can be used to normalize the concentration of the ACTH from the inferior petrosal sinuses in relation to the peripheral blood to yield a calculated ACTH in the inferior petrosal sinus-to-peripheral blood ratio that can enhance the diagnostic accuracy of the test. 33,65,93 For this reason, many centers save blood samples from the procedure and measure the prolactin concentrations if the results of the IPSS need further analysis. To avoid false-positive results, IPSS must be performed while the patient is hypercortisolemic.…”
Section: Diagnostic Evaluationmentioning
confidence: 99%
“…This hypothesis, based on the assumption that the hormones measured drained symmetrically in the two sides of the pituitary, was not consistently confirmed and conversely an intersinus, and central/peripheral gradient also for these hormones was repeatedly documented (96, 97, 98, 99). More recent reports on the use of PRL in addition to ACTH to correctly localize the pituitary adenoma site in CD have given conflicting result (100, 101). …”
Section: Bipss and Corticotroph Microadenoma Lateralizationmentioning
confidence: 99%